(untitled) - Metzger, Philip W. (Upper Saddle River, N.J., 1996)
With over 250,000 copies sold in its previous editions, this premier guide to managing software development has been updated in this third edition to account for increases in computer power, the use of software development tools, and object-oriented environments. Covers the analysis team and its work; the role of the manager, analyst, and programmer; the design process; the programming process; the system test process; and managing support people. For software programming managers, programmers, and lead technicians.
Keywords: Chương trình máy tính,Computer programming; Quản trị,Management